Membangun Kerukunan di Tengah Perbedaan : Praktik Resolusi Konflik di Tengah Gereja - Barbara Green Winslet Bessie; Daud Saleh Luji (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The church is called to bring about the harmony and unity of Christ in a divided world. However, internal conflict often arises from theological differences, leadership styles, cultural preferences, and interpersonal issues. Conflict that is not managed wisely can damage the integrity and witness of the church. This study uses a library research method and finds that harmony is an active process that requires dialogue, openness, acceptance, mutual respect, and love. The roots of church conflict are addressed through loving communication (Matthew 18), biblical mediation and negotiation training, cultivating a culture of forgiveness and reconciliation, and transparent and integrity-based leadership. Although challenges such as ego exist, the power of the gospel, the Holy Spirit, and the potential for growth offer great opportunities. A reconciling church is a powerful testimony of Christ's reconciling love.